Rapunzel, the one with all the hair eaudiobook - Mass, Wendy (Twice Upon a Time, 2020)
Rapunzel is having the ultimate bad day. She's been stolen by a witch, may have a ghost for a roommate, and doesn't even have a decent brush for her hair. Prince Benjamin's got it pretty tough, too. His father wants him to be more kingly, his mother wants him to never leave her sight, and his cousin wants to get him into as much trouble as possible (possibly with a troll). Both Rapunzel and Prince Benjamin are trapped—in very different ways. Once their paths cross, well, that's when things get really strange.